Coupled 3D time-dependent quantum wave-packet study of the O+OH reaction in hyperspherical coordinates on the CHIPR potential energy surface - Ghosh, Sandip; Sharma, Rahul; Adhikari, Satrajit; Varandas, António J.C. (Chemical physics letters, 2017)
[Display omitted] •Reactive scattering calculations for the O+OH reaction has been performed.•3D time-dependent wave packet formalism based on hyperspherical coordinates is used.•J-shifting scheme is employed to calculate thermal rate constants.•The thermal rate constants show good agreement with the experimental measurements and previous theoretical calculations. We report quantum dynamics calculations of the O+OH→H+O2 reaction on the CHIPR (Varandas, 2013) and DMBE IV (Pastrana et al., 1990) potential energy surfaces (PESs) for ground-state HO2 using the 3D time-dependent wavepacket formalism based on hyperspherical coordinates. Reaction probabilities for J=0 are calculated for several initial rovibrational states of the OH radical (v=0; j=0–5). The J-shifting approximation is used to obtain initial state selected rate-coefficients in the range 0–400K. Total and state-to-state rate-coefficients are predicted in good agreement with recent experimental studies and theoretical calculations.